Perceived Discrimination and Problems Faced by Gender and Sexual Minorities in Kathmandu - Ghimire, Sudha; Maharjan, Gyanu; Maharjan, Binita (Journal of Health Promotion, 2019)
Equality and freedom from discrimination are fundamental human right regardless of sexual orientation, gender identity. Despite a society that is moving forward in acceptance of differences, many young people still maintain uncomfortable and confused attitudes towards on-heterosexual lifestyles. Thus, this study was conducted to assess the perceived discrimination and problems faced by gender and sexual minorities in Kathmandu. Descriptive cross-sectional design and purposive sampling method was utilized to select sample. The study was conducted on Gender and sexual Minorities Forum Nepal, blue diamond society in Kathmandu from 17th July to 20 August 2018. Semi-structured self administered questionnaire was used to collect data, followed by some qualitative interview with selected participants. Among 112 respondents, almost half were gay, one third were transgender women and few were transgender men, lesbians and bisexuals. In work place more than half (69.1%) were verbally harassed, almost half (45.7%) were denied from job; one third (34.6%) were physically tortured. Majority of the respondents (80.5%) were verbally harassed in educational institutes, most of the respondents (91.7%) in public bathroom and public places, (84.6%) by police, almost half of all (49.4%) were physically tortured and (33.3%) were bullied in school. More than half (62.3%) were denied for house rent. Majority of the respondents (36.5%) accepted discrimination as a fact of life. Despite many supportive laws and provisions, LGBT people still face societal discrimination in Nepal. Thus, its humanitarian that sexual minorities are also a part of society and they have equal right to have dignified life.